2018
DOI: 10.1038/s41426-018-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an astrovirus causing fatal visceral gout in domestic goslings

Abstract: Astroviruses are recognized as a leading cause of gastroenteritis in humans and animals. They are also associated with extra-intestinal diseases, such as hepatitis in ducklings, nephritis in chickens, and encephalitis in cattle. In February 2017, a fatal infection of goslings characterized by visceral urate deposition was reported in the Shandong province, China. Our systematic investigation led to the isolation of an astrovirus, designated AAstV/Goose/CHN/2017/SD01, and similar disease was reproduced by exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 32 publications
8
108
0
Order By: Relevance
“…Astrovirus has been reported in poultry flocks, where it causes different clinical symptoms. Previous studies have revealed that gout in poultry was associated with ANV, CAstV and GoAstV field strain infections (Baxendale & Mebatsion, 2004;Bulbule et al, 2013;De Wit et al, 2011;Zhang, Cao, et al, 2018) In conclusion, this study described the isolation of a novel GoAstV strain, the SDXT strain, that caused visceral urate deposition in ducklings. Based on our genomic and phylogenetic analyses, the SDXT strain should be classified into a novel GoAstV group as a member of the Avastrovirus three species.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Astrovirus has been reported in poultry flocks, where it causes different clinical symptoms. Previous studies have revealed that gout in poultry was associated with ANV, CAstV and GoAstV field strain infections (Baxendale & Mebatsion, 2004;Bulbule et al, 2013;De Wit et al, 2011;Zhang, Cao, et al, 2018) In conclusion, this study described the isolation of a novel GoAstV strain, the SDXT strain, that caused visceral urate deposition in ducklings. Based on our genomic and phylogenetic analyses, the SDXT strain should be classified into a novel GoAstV group as a member of the Avastrovirus three species.…”
Section: Discussionmentioning
confidence: 64%
“…Astrovirus has been reported in poultry flocks, where it causes different clinical symptoms. Previous studies have revealed that gout in poultry was associated with ANV, CAstV and GoAstV field strain infections (Baxendale & Mebatsion, ; Bulbule et al, ; De Wit et al, ; Zhang, Cao, et al, ). Beginning in 2016, several novel GoAstVs emerged in gosling flocks in most goose‐breeding regions as major causative agents of diseases in geese, leading to huge economic losses in the poultry industry.…”
Section: Discussionmentioning
confidence: 98%
“…Novel HAstVs are part of the neurovirulent astroviruses, which also include animal astroviruses (30). Other unexpected clinical manifestations recently associated with human and animal astroviruses include respiratory tract infections (31)(32)(33)(34)(35)(36)(37), fever of unknown etiology (38,39), hepatitis (40,41), and severe gout in geese (42). Altogether, these findings suggest that there are probably other still unrecognized divergent astroviruses with clinical implications beyond gastroenteritis in humans and animals.…”
mentioning
confidence: 92%
“…ORF1a encodes non‐structural proteins, ORF1b encodes RNA‐dependent RNA polymerase, and ORF2 encodes nucleocapsid proteins. Avastrovirus (AAstV) isolated from avian species (Bulbule et al, ; Fu et al, ; Kaithal, Jindal, Kumar, & Mor, ; Mándoki, Dobos‐Kovács, Bakonyi, & Rusvai, ; Ter Veen, de Bruijn, Dijkman, & de Wit, ) is one of the leading causes of diseases in birds such as nephritis in chickens, hepatitis and stunting in ducks and gout in goslings (Bidin, Lojkic, Tisljar, Bidin, & Majnaric, ; Liu et al, ; Jin et al, ; Liu, Jiang, Dong, Wang, & Zhang, ; Yang, Tian, Tang, & Diao, ; Zhang, Cao, et al, ; Zhang, Wang, Liu, Yang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…diseases in birds such as nephritis in chickens, hepatitis and stunting in ducks and gout in goslings (Bidin, Lojkic, Tisljar, Bidin, & Majnaric, 2012;Liu et al, 2016;Jin et al, 2018;Liu, Jiang, Dong, Wang, & Zhang, 2018;Yang, Tian, Tang, & Diao, 2018;Zhang, Cao, et al, 2018;Zhang, Wang, Liu, Yang, & Zhang, 2017).…”
mentioning
confidence: 99%